2018
DOI: 10.1002/smll.201801542
|View full text |Cite
|
Sign up to set email alerts
|

Fluorination Triggered New Small Molecule Donor Materials for Efficient As‐Cast Organic Solar Cells

Abstract: Solution-processable small molecules (SMs) have attracted intense attention due to their definite molecular structures, less batch-to-batch variation, and easier structure control. Herein, two new SM donors based on substituted isatin unit (DI3T, DI3T-2F) are synthesized and applied as electron donors with the mixture of PC BM to construct organic photovoltaics. As a result, 5,6-difluoro isatin derivative (DI3T-2F) obtains a power conversion efficiency of 7.80% by a simple solution spin-coating fabrication pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 57 publications
0
15
0
Order By: Relevance
“…crystallinity and facilitate charge transport. [22][23][24][25][26][27][28] Moreover, comparing the 1,1-dicyanomethylene-3-indanone (IC) endgroup with its fluorinated derivative 2-(5,6-difluoro-3oxo-2,3-dihydro-1H-inden-1-ylidene)malononitrile (IC-4F), the stronger electron-withdrawing effect of the latter can enhance intramolecular charge transfer (ICT) in NFA materials resulted in a red-shift of the absorption spectra of NFAs to the near-IR region, thus enhancing device photocurrent. Several studies have demonstrated that OSCs based on ladder type NFAs with fluorinated endgroups show improved device performance than those based on non-fluorinated counterparts.…”
Section: Intramolecular Interactions Through Noncovalent C−f•••s and mentioning
confidence: 99%
“…crystallinity and facilitate charge transport. [22][23][24][25][26][27][28] Moreover, comparing the 1,1-dicyanomethylene-3-indanone (IC) endgroup with its fluorinated derivative 2-(5,6-difluoro-3oxo-2,3-dihydro-1H-inden-1-ylidene)malononitrile (IC-4F), the stronger electron-withdrawing effect of the latter can enhance intramolecular charge transfer (ICT) in NFA materials resulted in a red-shift of the absorption spectra of NFAs to the near-IR region, thus enhancing device photocurrent. Several studies have demonstrated that OSCs based on ladder type NFAs with fluorinated endgroups show improved device performance than those based on non-fluorinated counterparts.…”
Section: Intramolecular Interactions Through Noncovalent C−f•••s and mentioning
confidence: 99%
“…For instance, PCE improvements can clearly be seen in the cases of IDT‐T (6.28%) versus IDTT2F (8.75%), INPIC (4.31%) versus INPIC‐4F (13.13%), IDT2Se (9.36%) versus IDT2Se‐4F (11.19%), ITVIC (7.34%) versus ITVffIC (10.54%), and ITIC (11.05%) versus IT4F (13.10%) . In addition, fluorination on small‐molecule donors also dramatically improves the fullerene‐based ASM OSCs, for example, DI3T (0.83%) versus DI3T (7.80%) and BTID‐0F (8.30%) versus BTID‐2F (11.30%) . However, such a facile yet effective strategy has rarely been applied in FREA‐based ASM OSCs, and the effect of fluorination of FREAs on high‐performance ASM OSCs is still unclear and requires further investigation.…”
Section: Introductionmentioning
confidence: 99%
“…Several groups have reported that the ternary or process‐engineering strategy is useful to fabricate thick active films with good PCEs . To be noted, most of these devices are based on fullerene derivatives (PC 71 BM or PC 61 BM) as electron acceptor on consideration of their excellent electron mobility and isotropic charge transport property.…”
Section: Introductionmentioning
confidence: 99%